Des cultures politiques situées à un environnementalisme ordinaire commun dans les jardins partagés - Victoria Sachsé (Développement Durable et Territoires)
Through the exploration of two shared gardens, one in Rome and the other in Strasbourg, we highlight the diversity of political cultures that animate these different spaces. Indeed, the qualitative survey carried out during the course of a thesis – mainly participant observations and interviews – reveals distinct cultural and political imaginaries depending on the local context. In Rome, the garden is characterised by a dynamic of appropriation of public space through a situation of partial conflict with local institutions, which reveals itself to be a form of expression of the right to the city, whereas in Strasbourg the installation dynamic discovers a form of an alliance between the association and the institutions through the realisation of a shared permaculture garden. Nevertheless, these gardens remain bearers of similar practices, some of whose dynamics seem to transcend these geographical, political and social distinctions and can be read, through the prism of ordinary environmentalism, as reconfigurations of the relationship between humans and non-humans in the Anthropocene era.